(untitled) (Research, Society and Development, 2022)
Brazil is a country with a large party of the population, including traditional communities, that use plants for medicinal purposes, however, the prospect of drugs derived from plants is still little explored. The present study aimed to carry out a systematic review of the literature, in an attempt to understand how studies involving ethnopharmacology have developed in Brazil during the 21st century. The Scielo and PubMed data bases were used, using the keywords “ethnopharmacology” and “Brazil”. In a total of 212 articles were selected and the highest number of publications in the years of, respectively: 2018 (9.43%), 2020 (8.96%) and 2014 (8.96%). Experimental studies (laboratory studies, such as phytochemicals and biological activity) accounted 41.98% of the total, followed by literature reviews (36.32%) and ethno-directed interviews (20.28%). The results showed that the most common types of studies were popular use and biological activity (33.96%), followed by studies of popular use, phytochemical composition and biological activity (21.70%) and ethno-directed survey (20.75%). The most cited botanical families were Fabaceae (8.49%), Asteraceae (5.19%) and Lamiaceae (2.83%) and the main biological activities evaluated were anti-inflammatory (10.85%), antimicrobial (10 .85%), antimalarial (5.19%) and antioxidant (4.72%). Among the traditional communities surveyed were rural communities (50%) and quilombola communities (13.64%). The present study indicates that there was a significant increase in publications involving ethnopharmacology in Brazil, mainly from 2010, associated with a greater diversification of the researched objectives.